Cosmological Neuroscience on the Relationship Between the Evolutionary Levels of Consciousness and the Multidimensional Nature of Soul: Consciousness as the neural environment of Soul - Ludvig, Nandor (Journal of NeuroPhilosophy, 2024)
While the nature of Consciousness is one of the most intensely debated subjects of current neuroscience, the nature of Soul is hardly represented in the textbooks of the field, if represented at all. As a consequence, the relationship between the two phenomena remains unclear. This work took a look into that relationship from the vantage point of cosmological neuroscience. The following concept emerged: Consciousness seems to be the evolutionary product of a cosmic blueprint for animal central nervous systems allowed to become neural environments sensing the host’s body and surrounding world to such extent that these neural environments once could house the distinct cellular network of the Animal Soul, which, evolving further, gave rise to the leap of the Human Soul with its prefrontal cortical neural supercircuitry now creating the digitized Noospheric Soul with its potential to sense its cosmic origin.